PENERAPAN JUS COGENS TERHADAP PRAKTIK IMUNITAS NEGARA (STUDI KASUS PUTUSAN ICJ DALAM KASUS JERMAN LAWAN ITALIA) - Lantang, Immanuela (LEX CRIMEN, 2013)
Cases related to foreign state immunity and jus cogens arise with a variety of different decisions - different in the practice of the state - state makes this area blurred and the create uncertainty of law under international law. The conflict of the two rules reached the top when Germany sued Italy on December 23, 2008 before the International Court of Justice / ICJ which confirmed that Italy, through the practice of law, violated its obligations towards Germany under international law. Applications made ​​by Germany on the basis of the decision of the Corte di Cassazione Italy on March 11, 2004 in the Ferrini case, the case where Italian court declared that Italy may exercise jurisdiction over Germany in connection with a lawsuit brought by a man who had been deported to Germany during World War II. Since the release of the decision, Germany confirmed that there are so many similar processes are brought in the Court of Italy by people who also suffered losses due to World War II. Germany asked the ICJ to declare that the Italian Republic must take any necessary steps to ensure that in the future no longer an Italian court to take legal action against Germany by accepting the claims of its citizens against the German civilian population on the basis of violations of international norms during World War II. Keywords: the rule of state immunity